Bovine colostrum supplementation as a new perspective in depression and substance use disorder treatment: a randomized placebo-controlled study - Durkalec-Michalski, Krzysztof; Główka, Natalia; Podgórski, Tomasz; Odrobny, Weronika; Krawczyński, Marcin; Botwina, Ryszard; Bodzicz, Stanisław; Nowaczyk, Paulina M. (Frontiers in Psychiatry, 2024)
This randomized, placebo-controlled, double-blind, parallel study aimed to evaluate the effect of 3month supplementation of bovine colostrum (BOV-COL; 8x400 mg per day) on the outcomes of depression treatment in hospitalized patients with substance use disorder (SUD). The hypothesis is that BOV-COL supplementation as an add-on treatment results in favorable alternations in selected blood inflammatory markers or neurotransmitters, leading to better depression treatment outcomes compared with placebo (PLA). Patients with a Minnesota Multiphasic Personality Inventory-2 score ≥60 points were enrolled. Twenty-nine participants (n=18 in the BOV-COL group and n=11 in the PLA group) completed the protocol.